Strategi Investasi Asing Dalam Meningkatkan Produksi Maupun Infrastruktur - Budi Iriani Yudaningrum,; Koslani, (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2024)
Investment is an important instrument and driving force in development because it is the first step in economic development. In developing countries, investment is urgently needed and has an important role in accelerating development because it is a tool for increasing income and employment growth, improving technology, and fostering socio-economic development. This study aims to analyze the effect of foreign direct investment (FDI) on the economy in Indonesia. This study uses descriptive analysis, namely by analyzing various reading literature, both book and journal literature, as well as other literature that is considered relevant, and drawing a conclusion. The results showed that foreign direct investment (FDI) obtained a positive and significant effect on the Indonesian economy. This means that any increase in foreign investment (FDI) will result in an increase in the Indonesian economy. Based on the research results, it is suggested that the Indonesian government should maintain the stability of economic variables that can stimulate foreign investment in order to achieve sustainable economic growth.